Extrusion bioprinting of hydroxyethylcellulose-based bioink for cervical tumor model. (15th May 2021) - Gospodinova, Antonina; Nankov, Vladislav; Tomov, Slavcho; Redzheb, Murad; Petrov, Petar D.
Highlights: Sodium Alginate (SA) in hydroxyethylcellulose(HEC)-SA blends reduces the yield stress. Increasing SA content first decreases and then increases the blend's viscosity. During bioprinting, HeLa viability is most negatively affected by the HEC-SA extrusion. Mixing HeLa with HEC-SA gels results in lower cell death than the extrusion printing. Bioprinting up to 90 min does not affect HeLa viability at low alginate content. Abstract: The present study demonstrates the extrusion printing of highly viscous and thixotropic hydroxyethylcellulose-based bioinks blended with various concentrations of sodium alginate (SA) and embedded with HeLa cells. The cell viability is shown to be inversely proportional to the relative SA content and can be as high as 81.5 % following one day of incubation. Furthermore, the biocompatibility of the hydrogel matrix supports cell proliferation resulting in an order of magnitude larger number of cells after a 7-day incubation. The cell viability is negatively affected mostly by the extrusion printing itself with some cell death occurring during their embedding in the hydrogels. After embedding the HeLa cells in the blends containing 1 and 2.5 % SA, the cell viability is not significantly affected by the residence time of up to 90 min before the bioink extrusion. The printed constructs can be utilized as a cervical tumor model.